Molecular basis and genetics of hypohidrotic ectodermal dysplasias - V. A. Kovalskaia; T. Cherevatova; A. V. Polyakov; O. P. Ryzhkova (Вавиловский журнал генетики и селекции)
Ectodermal dysplasia (ED) is a heterogeneous group of hereditary diseases of the skin and its appendages, which are characterized by impaired development and/or homeostasis of two or more ectoderm derivatives, including: hair, teeth, nails, sweat glands and their modifications (mammary glands, for instance). The overall prevalence of ectodermal dysplasia remains precisely unknown not only in Russia, but also in the world, nor is known the contribution of individual genes to its structure. This complicates the DNA diagnosis establishment of this disease due to the lack of an accurate diagnostic algorithm and a universal cost-effective method of analysis. To date, the most highly-researched genes involved in the development of anhydrous or hypohidrotic forms of ED are EDA, EDAR, EDARADD and WNT10A. The ectodysplasin A (EDA) gene is the cause of the most common X-linked form of ED, a gene from the Wnt family (WNT10A) is responsible for the autosomal recessive form of the disease, and two other genes (EDAR and EDARADD) can cause both autosomal recessive and autosomal dominant forms. This review provides the characteristics of the genes involved in ED, their mutation spectra, the level of their expression in human tissues, as well as the interrelation of the aforementioned genes. The domain structures of the corresponding proteins are considered, as well as the molecular genetic pathways in which they are involved. Animal models for studying this disorder are also taken into consideration. Due to the cross-species genes conservation, their mutations cause the disruption of the development of ectoderm derivatives not only in humans, but also in mice, cows, dogs, and even fish. It can be exploited for a better understanding of the etiopathogenesis of ectodermal dysplasias. Moreover, this article brings up the possibility of recurrent mutations in the EDA and WNT10A genes. The review also presents data on promising approaches for intrauterine ED treatment.